The presidents and the people : five leaders who threatened democracy and the citizens who fought to defend it - Brettschneider, Corey Lang (W. W. Norton & Company, 2024)
This meticulously researched account of assaults on democracy by five presidents who imprisoned critics, spread a culture of white supremacy and committed crimes with impunity shows how citizens like Frederick Douglass, Ida B. Wells and Daniel Ellsberg fought back against presidential abuses of power.